Analysis of performance and economic value of thin film and monocrystalline photovoltaic systems in the tropical area of Jakarta - Novagia Adita; Setiawan, Eko Adhi (International Journal of Electrical, Computer, and Biomedical Engineering, 2023)
Evaluation of PV performance is important as a development in supporting the government’s program to increase the renewable energy mix to reach 23% in 2025. This study aims to analyze the performance of thin film vs monocrystalline PV which has been operating in tropical areas in Jakarta. Then thin film and monocrystalline PV were simulated using PVsyst. Evaluation is carried out through a performance ratio analysis approach and the value of the degradation rate. The performance of thin film PV was 5% close to the simulation result but not for the monocrystalline silicon. The degradation rates for thin-film and mono-si were 0.93% and 2.07%, respectively. The degradation rates of PV are comparable to other studies that have been conducted in other countries with similar climates. Such a degradation rate value reduces the economic value of PV where the Levelized Cost of Energy (LCOE) value obtained decreases for thin films by 25% while for monocrystalline would change by 77%.